Etnobotani Tanaman Pangan dari Masyarakat Desa Mekar Pelita Kecamatan Sayan Kabupaten Melawi - Firdawati, Kiki; Syamswisna, Syamswisna; Fajri, Hayatul (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Vegetable food is very important for the sustainability of human life. Various types of plants from Mekar Pelita Village in Melawi Regency, West Kalimantan Province, are used as food sources. This study aims to determine the types of plants used as food sources for the community in Mekar Pelita Village, Melawi Regency, West Kalimantan Province. Data collection techniques used interviews, observations (observations), and plant identification. The source of the informant was determined by purposive sampling technique. Based on the results of the study, it was found that 66 species of plants from 39 families were used as food sources by the people of Mekar Pelita Village. These plants are consumed as vegetables, cooking spices, snacks, the main carbohydrate source (rice), or consumed directly. Furthermore, the residents of Mekar Pelita Village have three types of typical plants that are used as food additives. Czechuk leaves (Sapindaceae) are used as a flavor enhancer, because they give a taste like shrimp paste, Kesopang leaves (Piperaceae) are used as food seasoning, and Kerutau (Morus sp.) are used to give a sweet taste (sugar substitute). Another distinctive species found in Mekar Pelita Village is Kelopuk. Kelopuk leaves (Malvaceae) are consumed by nursing mothers to improve the quality of breast milk.